(untitled) (Bangladesh Journal of Zoology, 2022)
Oryza sativa (L.) is one of the world’s most important crop providing staple food for nearly half of the global population. Rice is subjected to considerable damage by a number of grasshoppers. The accurate identification of pest species is a crucial step for the appropriate application of control measures. Molecular characterization and DNA barcoding of grasshopper pests of rice was performed in the present research work. Six species of grasshopper pests were identified from different paddy fields using COI gene sequences. Among the sequences the A+T content (64.2%) was higher than the G+C (35.8%) content. The interspecific genetic distance ranged between 13 and 34%. The haplotype analysis of Conocephalus exemptus showed highest (110) mutated sites among the analyzed species. Both the Maximum likelihood and Neighbor-joining phylogenetic tree construction showed two distinct clades of short-horned and long-horned grasshoppers. C. exemptus was found in another monophyletic group. Our results demonstrate that DNA barcoding is likely to be a powerful tool for identifying and understanding grasshopper evolution. Bangladesh J. Zool. 50 (2): 217-229, 2022